2015
DOI: 10.1021/acs.jpcb.5b00743
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Specific High-Affinity Binding of Cucurbit[7]uril to Amino Acids in Water

Abstract: This work presents a systematic study on the host-guest interactions between the macrocyclic host molecule cucurbit[7]uril (CB[7]) and amino acids (AAs) including three basic AAs (Lys, Arg, and His) and three aromatic AAs (Phe, Tyr, and Trp) to elucidate the origin of the high selectivity of CB[7] toward AA residues in proteins. Complex formation between CB[7] and each AA was examined in solution (by isothermal titration calorimetry and NMR) as well as in the gas phase (by ion mobility mass spectrometry and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
115
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 60 publications
5
115
0
Order By: Relevance
“…The first characterized family member, cucurbit[6]uril, has six glycoluril units, and subsequent synthetic efforts led to the five-, seven-, eight- and ten-monomer versions, cucurbit[n]uril (n=5,6,7,8,10) (71), which have been characterized to different extents. Of note, the n=6,7,8 variants accommodate guests of progressively larger size, but are consistent in preferring to bind guests with a hydrophobic core sized to fit snugly into the relatively nonpolar binding cavity, along with at least one cationic moiety (though neutral compounds do bind (134, 63)) that forms stabilizing interactions with the oxygens of the carbonyl groups fringing both portals of the host (71). Although derivatives of these parent compounds have been made (64, 124, 3, 24), most of the binding data published for this class of hosts pertain to the non-derivatized forms.…”
Section: Benchmark Systems For Binding Predictionmentioning
confidence: 75%
“…The first characterized family member, cucurbit[6]uril, has six glycoluril units, and subsequent synthetic efforts led to the five-, seven-, eight- and ten-monomer versions, cucurbit[n]uril (n=5,6,7,8,10) (71), which have been characterized to different extents. Of note, the n=6,7,8 variants accommodate guests of progressively larger size, but are consistent in preferring to bind guests with a hydrophobic core sized to fit snugly into the relatively nonpolar binding cavity, along with at least one cationic moiety (though neutral compounds do bind (134, 63)) that forms stabilizing interactions with the oxygens of the carbonyl groups fringing both portals of the host (71). Although derivatives of these parent compounds have been made (64, 124, 3, 24), most of the binding data published for this class of hosts pertain to the non-derivatized forms.…”
Section: Benchmark Systems For Binding Predictionmentioning
confidence: 75%
“…1a) are a family of unique macrocyclic cavitands possessing two identical carbonyl-laced portals and a rigid hydrophobic cavity, which can selectively accommodate and interact with various organic molecules1314151617. In the past decade, Q[ n ]s have been exploited for binding amino acids, peptides and proteins181920212223242526272829303132333435. For example, Urbach and co-workers studied the combining power of Q[7] to a number of amino acids, peptides and proteins, and found that the Q[7] prefer to bind guests containing an N-teminal aromatic residue18192021.…”
mentioning
confidence: 99%
“…For example, Urbach and co-workers studied the combining power of Q[7] to a number of amino acids, peptides and proteins, and found that the Q[7] prefer to bind guests containing an N-teminal aromatic residue18192021. Kim group systematically studied the binding properties of Q[7] to a series of amino acids in both solution and the gas phase28. Scherman et al .…”
mentioning
confidence: 99%
“…[1][2][3] Monoclonal antibodies are characterized by tight and specific binding,l ow toxicity,a nd immunogenicity, however, it is often difficult to develop suitable conjugation chemistry to drugs of interest, without losing any potency, and still retaining ahigh production yield. [5][6][7][8][9][10][11] In particular, several examples of interactions of peptides and proteins with different members of the cucurbit[n]uril (CB[n]) family have been reported, [12][13][14][15][16][17][18][19] however, they have mainly been restricted to N-termini. [5][6][7][8][9][10][11] In particular, several examples of interactions of peptides and proteins with different members of the cucurbit[n]uril (CB[n]) family have been reported, [12][13][14][15][16][17][18][19] however, they have mainly been restricted to N-termini.…”
mentioning
confidence: 99%
“…[1,4] In the last few years, host-guest chemistry has played an important role in tether-ing peptides and proteins together,o pening new approaches towards biomedical targets. [5][6][7][8][9][10][11] In particular, several examples of interactions of peptides and proteins with different members of the cucurbit[n]uril (CB[n]) family have been reported, [12][13][14][15][16][17][18][19] however, they have mainly been restricted to N-termini. CB[n]s are af amily of macrocyles prepared by condensation of glycouril at high temperature under acidic conditions.…”
mentioning
confidence: 99%